Costus pictus D.Don.ex Lindl. new records to flora of Maharashtra, India. - A, Kare M; Mule, D A; Paithane, V A; Bhuktar, A S (International Multidisciplinary Research Journal, 2013)
During the field survey in Paithan Tehshil of Aurangabad District some Specimens were collected and identified Costus pictus D.Don ex Lindl which was not recorded for Flora of Maharashtra so far. This paper records them with updated nomenclature, descriptions and note on phenology and Images for its easy identity.